1988
DOI: 10.1002/pd.1970080305
|View full text |Cite
|
Sign up to set email alerts
|

Microvillar enzyme assays in amniotic fluid and fetal tissues at different stages of development

Abstract: A systematic study of microvillar enzyme activities in the amniotic fluid in correlation with their values in different fetal tissues during development has been undertaken. Microvillar enzymes appeared in the amniotic fluid at the time of disappearance of the anal membrane, 12-13 weeks, and declined from the 18th week until the 24th week. The study of fetal tissues and fluids has shown that gamma-glutamyltranspeptidase is mainly of liver origin. The significant decrease of the activities of these amniotic flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
46
1
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 14 publications
2
46
1
1
Order By: Relevance
“…But after 24 weeks of gestation, it is no longer possible to differentiate between abnormally low and physiologically low levels of the enzymes, although high values exclude biliary atresia and cystic fibrosis. In biliary atresia, amniotic fluid GGTP levels alone drop dramatically from 16 weeks of gestation (Muller et al, 1991), whereas in cystic fibrosis, or intestinal atresia, levels of all the digestive enzymes fall sharply (Brock, 1983;Carbarns et al, 1983;Muller et al, 1988;Ochshorn et al, 2007). The latter profile, typical of cystic fibrosis, was seen in case no.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…But after 24 weeks of gestation, it is no longer possible to differentiate between abnormally low and physiologically low levels of the enzymes, although high values exclude biliary atresia and cystic fibrosis. In biliary atresia, amniotic fluid GGTP levels alone drop dramatically from 16 weeks of gestation (Muller et al, 1991), whereas in cystic fibrosis, or intestinal atresia, levels of all the digestive enzymes fall sharply (Brock, 1983;Carbarns et al, 1983;Muller et al, 1988;Ochshorn et al, 2007). The latter profile, typical of cystic fibrosis, was seen in case no.…”
Section: Discussionmentioning
confidence: 78%
“…In the present study, amniotic fluid digestive enzymes assays were performed in two of the four cases (amniocentesis not performed in one case and enzymes were not assayed in the other). The value of amniotic fluid digestive enzymes has been previously described (Carbarns et al, 1983;Muller et al, 1988). These digestive enzymes, which are synthesized by the biliary epithelium (GGTP) and by enterocytes [intestinal alkaline phosphatase (ALP)], are present in the amniotic fluid from 12 to 13 weeks of gestation, a period corresponding to the resorption of the anal membrane, and then rise to a plateau at 17-18 weeks, before gradually decreasing to 24 weeks, because the progressive maturation of the anal sphincter muscles makes the anus impermeable to digestive secretions around 24 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study based on a series of 44 cases of EA, we observed that amniotic fluid (AF) biochemistry had potential additional value in prenatal diagnosis, with a significant difference for total protein, α-fetoprotein, and γ-glutamyl transpeptidase (GGTP) between the EA group (whatever the anatomical type) and the control group (12). These markers are part of AF biochemical patterns used for prenatal diagnosis of different gastrointestinal diseases as previously described (13,14). The AF digestive enzymes (AF-DEs) we assayed, GGTP, l-leucine-aminopeptidase (AMP), and intestinal alkaline phosphatase (iALP), are secreted by microvilli.…”
mentioning
confidence: 99%
“…The AF digestive enzymes (AF-DEs) we assayed, GGTP, l-leucine-aminopeptidase (AMP), and intestinal alkaline phosphatase (iALP), are secreted by microvilli. Previous studies of fetal tissues had specified the location of each enzyme: biliary epithelia for GGTP, proximal small bowel for AMP, and distal small bowel for iALP (14). AF-DE patterns are related to the physiological maturation of the fetal digestive tract.…”
mentioning
confidence: 99%
See 1 more Smart Citation